2004
DOI: 10.1021/ol0491078
|View full text |Cite
|
Sign up to set email alerts
|

Short Synthesis of the 6,6-Spiroketal Cores of Spirofungins A and B

Abstract: [reaction: see text] Initial efforts toward the total synthesis of the antifungal antibiotics spirofungins A and B are reported. A short and efficient synthesis of the C9-C20 6,6-spiroketal fragments of both compounds is described. This asymmetric approach uses a very efficient alkylation of a lithiated N,N-dimethylhydrazone followed by spiroketal formation under acidic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…In addition,equatorial methyl groups at the 2-or 8-position appear at lower field in the 13 C spectrum than axial methyl groups. [32] In all mixtures the configuration with bisaxial arrangement of the spiro C À O bonds was favoured ( Table 1). The minor isomer is expected to adopt configuration B or C stabilised by only one anomeric effect (Scheme 7).…”
Section: Dedicated Cluster Full Papersmentioning
confidence: 97%
“…In addition,equatorial methyl groups at the 2-or 8-position appear at lower field in the 13 C spectrum than axial methyl groups. [32] In all mixtures the configuration with bisaxial arrangement of the spiro C À O bonds was favoured ( Table 1). The minor isomer is expected to adopt configuration B or C stabilised by only one anomeric effect (Scheme 7).…”
Section: Dedicated Cluster Full Papersmentioning
confidence: 97%
“…104 A very efficient alkylation of a lithiated N,N-dimethylhydrazone of a chiral ketone (33, R 2 ) Me, R 1 ) CH 2 CH(Me)-CH(O(TBS))CH 2 O(PMB)) followed by spiroketal formation under acidic conditions was also used in a short synthesis of the 6,6-spiroketal fragments 38 and 39 useful for synthesis of the antifungal antibiotics spirofungins A and B. 105 Another alkylation reaction of the lithiated N,N-dimethylhydrazones of elaborate methyl ketones 33 (R 1 ) H, R 2 ) chiral O-protected substituted trihydroxynonyl) with suitable, protected iodide 40 afforded linear spiroketal intermediates. After functional group adjustment, these advanced intermediates were cyclized to their respective spiroketals 41 (R ) H, R ) Me), which constituted subunits in the asymmetric synthesis of the macrolide antibiotics (+)-rutamycin B and (+)-oligomycin.…”
Section: Alkylation Of Nn-dimethylhydrazonesmentioning
confidence: 99%
“…It was also observed that each isolated pure spiroketal led to the same 30:70 equilibrium mixture under very mild acidic conditions (CDCl 3 ).
23 Synthesis of the Spiroketal Segment of Spirofungins A and B by Dias et al
…”
Section: 2 Polyketide Antibiotics With a Nonanomeric [66]-spiroketal ...mentioning
confidence: 99%